Supporting return to work after psychiatric hospitalization—A cluster randomized study (RETURN-study). Issue 1 (9th January 2023) - Hamann, Johannes; Lang, Anne; Riedl, Lina; Blank, Daniela; Kohl, Monika; Brucks, Adele; Goretzko, David; Bühner, Markus; Waldmann, Tamara; Kilian, Reinhold; Falkai, Peter; Hasan, Alkomiet; et al.
Abstract: Background: If people with episodic mental-health conditions lose their job due to an episode of their mental illness, they often experience personal negative consequences. Therefore, reintegration after sick leave is critical to avoid unfavorable courses of disease, longer inability to work, long payment of sickness benefits, and unemployment. Existing return-to-work (RTW) programs have mainly focused on "common mental disorders" and often used very elaborate and costly interventions without yielding convincing effects. It was the aim of the RETURN study to evaluate an easy-to-implement RTW intervention specifically addressing persons with mental illnesses being so severe that they require inpatient treatment. Methods: The RETURN study was a multi-center, cluster-randomized controlled trial in acute psychiatric wards addressing inpatients suffering from a psychiatric disorder. In intervention wards, case managers (RTW experts) were introduced who supported patients in their RTW process, while in control wards treatment, as usual, was continued. Results: A total of 268 patients were recruited for the trial. Patients in the intervention group had more often returned to their workplace at 6 and 12 months, which was also mirrored in more days at work. These group differences were statistically significant at 6 months. However, for the main outcome (days at work at 12 months), differences were no longer statistically significant ( p = 0.14). Intervention patients returned to their workplace earlier than patients in the control group ( p = 0.040). Conclusions: The RETURN intervention has shown the potential of case-management interventions when addressing RTW. Further analyses, especially the qualitative ones, may help to better understand limitations and potential areas for improvement.